Development of a Popular Scientific Book on the Population Structure of Plant Stands along the Aluh-Aluh River - Riya Irianti; Dharmono Dharmono; Mahrudin Mahrudin; Muhammad Zaini (Universitas Lambung Mangkurat, 2025)
The purpose of this study was to describe the validity and practicality of the Popular Scientific Book on the population structure of stands on the banks of the Aluh-Aluh River, Simpang Warga Village, Banjar Regency. Development using the Plomp and Nieveen model consisting of 3 stages, namely 1) preliminary research; 2) Prototyping Stage; and 3) Assessment Phase. Validation and readability tests using validity and readability test questionnaire instruments and practicality tests using practicality test questionnaire instruments. The validity of the Popular Scientific Book developed obtained a score from 3 validators of 92.05% with very valid criteria, indicating that the BIP developed structurally and procedurally is suitable for use in learning Plant Ecology courses as enrichment material. The readability of the Popular Scientific Book from 3 students obtained a score of 94.4% with very good criteria. The practicality of the Popular Scientific Book developed obtained a score of 97% with the criteria of very practical from 6 students, meaning that the Popular Scientific Book developed according to students is easy to use or very practical to use in learning the Plant Ecology course as enrichment material.